PENINGKATKAN PENGETAHUAN DAN KETERAMPILAN PADA KADER POSYANDU MELALUI PELATIHAN PIJAT BAYI ( BABY MASSAGE ) DI DESA DOMAS KABUPATEN GRESIK - Handajani, Diani Octaviyanti; Suprapti, Suprapti (Universitas Muhammadiyah Tapanuli Selatan, 2020)
Children's health, especially babies and toddlers are one of the priority aspects to be considered; providing stimulation to children is one that can do to deliver growth and development. The stimulus provided is to give a baby massage or baby massage. Domas Village has a limitation on mothers' knowledge and skills for baby massage. The need for learning and training about baby massage so that mothers can have their baby massage. The purpose of community service is to help cadre mothers provide knowledge of baby massage and help cadres learn baby massage techniques so that cadre mothers can apply the command given to mothers in Domas village. The result of community service is that this activity went smoothly attended by 20 cadre mothers, and 20 cadre mothers or 100% can understand and do baby massage or baby massage.